Beyond the innovator's Dilemma: The process and effect of fintech regulatory environment - Geoffrey Otieno; Ruth Kiraka (Cogent Business & Management, 2023)
Previous research has established that certain characteristics of lead users, such as their ability to identify trends and the benefits they expect from an innovation, are important in determining the success of an innovation. However, the role of regulatory authorities and the innovation process in influencing innovation outcomes has not been thoroughly explored. This study aims to fill this gap by examining the impact of these factors on innovation success, using a mixed-method approach. Data were collected from 321 lead users and eight regulators through both quantitative and qualitative surveys, and analyzed using SPSS and NVivo. The results show that the number of partners involved in the innovation process is a significant factor, whereas work experience has an impact only when considered in conjunction with other variables. This study contributes to the understanding of lead user innovation by demonstrating that factors beyond just trends and benefits can influence the success or failure of innovation and provides new insights into the role of the innovation process and regulatory authorities.
Keywords: 650; innovation; lead-users; moderator; regulator